Four Metaphors of Modernism : From der Sturm to the Société Anonyme - Anger, Jenny (University of Minnesota Press, 2018)
Cover -- Half Title -- Title -- Copyright -- Contents -- Overture -- ACT ONE Piano -- ACT TWO Water -- ACT THREE Glass -- ACT FOUR Home -- Reprise -- Acknowledgments -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z.